ADDRESSING LEGAL ISSUES IN THE GLOBALISATION OF ECOTOURISM IN MALAYSIA - ABDULLAH, NURAISYAH CHUA (ITB Journal Publisher, LPPM ITB, 2008)
Some environmentalists argue that the process of globalisation which has resulted in trade liberalisation, accelerates economic growth and development, and that this promotes polluting activities and speeds the depletion ofnonrenewable resources (A. Y Seita, 1999). Since Malaysia is one of the signatories of the General Agreement on Trade in Services (GATS) and ASEAN Framework Agreement on Services (AFAS) which provides equal investment opportunities to foreign investors as domestic service providers including ecotourism, this article explores the legal issues that arise in the globalization of ecotourism.